Characterization of a CdZnTe detector for a low-power CubeSat application. (1st August 2022) - Lucchetta, Giulio; Ackermann, Markus; Berge, David; Bloch, Ingo; Bühler, Rolf; Kolanoski, Hermann; Lange, Wolfgang; Zappon, Francesco
Abstract: We report spectral and imaging performance of a pixelated CdZnTe detector custom designed for the MeVCube project: a small Compton telescope on a CubeSat platform. MeVCube is expected to cover the energy range between 200 keV and 4 MeV, with a sensitivity comparable to the one of the last generation of larger satellites. In order to achieve this goal, an energy resolution of few percent in full width at half maximum (FWHM) and a 3-D spatial resolution of few millimeters for the individual detectors are needed. The severe power constraints present in small satellites require very low power read-out electronics for the detector. Our read-out is based on the VATA450.3 ASIC developed by Ideas, with a power consumption of only 0.25 mW/channel, which exhibits good performance in terms of dynamic range, noise and linearity. A 2.0 cm× 2.0 cm× 1.5 cm CdZnTe detector, with a custom 8 × 8 pixel anode structure read-out by a VATA450.3 ASIC, has been tested. A preliminary read-out system for the cathode, based on a discrete Amptek A250F charge sensitive pre-amplifier and a DRS4 ASIC, has been implemented. An energy resolution around 3% FWHM has been measured at a gamma energy of 662 keV; at 200 keV the average energy resolution is 6.5%, decreasing to ≲ 2% at energies above 1 MeV. A 3-D spatial resolution of ≈ 2 mm is achieved in each dimension.